2017
DOI: 10.18632/oncotarget.19145
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair deregulation in discrete prostate cancer lesions identified on multi-parametric MRI and targeted by MRI/ultrasound fusion-guided biopsy

Abstract: Prostate cancer is histologically and molecularly heterogeneous. Clinically significant disease is often driven by dominant intra-prostatic lesions (IPLs). Prostate cancers cluster into molecular phenotypes with substantial genetic heterogeneity making pathway-based molecular analysis appealing. MRI/ultrasound fusion biopsy provides a unique opportunity to characterize tumor biology of discrete lesions at diagnosis. This study determined the feasibility of pathway-based gene expression analysis of prostate bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…DNA damage repair pathway defects play an important role in prostate cancer carcinogenesis and progression, and mutations are present in around 19% of prostate tumours of Gleason grade ≥ 8 [31] ; these also appear to play a role in tumour conspicuity on mpMRI. Dulaney et al [27] noted significantly higher deregulation of DNA repair–related genes in mpMRI-visible targeted tumours with higher dynamic contrast enhancement values, as also noted in other studies [26] . Another case study found lower ADC values in tumour regions with a greater number of copy-number alterations and higher mutational burden [32] .…”
Section: Evidence Synthesissupporting
confidence: 68%
See 1 more Smart Citation
“…DNA damage repair pathway defects play an important role in prostate cancer carcinogenesis and progression, and mutations are present in around 19% of prostate tumours of Gleason grade ≥ 8 [31] ; these also appear to play a role in tumour conspicuity on mpMRI. Dulaney et al [27] noted significantly higher deregulation of DNA repair–related genes in mpMRI-visible targeted tumours with higher dynamic contrast enhancement values, as also noted in other studies [26] . Another case study found lower ADC values in tumour regions with a greater number of copy-number alterations and higher mutational burden [32] .…”
Section: Evidence Synthesissupporting
confidence: 68%
“…Li and colleagues [26] reported enriched processes of mitotic cell cycle, protein folding, cell cycle, mitotic cell cycle process, and cell division in mpMRI-visible cancers. Furthermore, Dulaney and colleagues [27] reported that tumours with a PI-RADS score of 5 had significantly more deregulation of pathways involved in apoptosis and cell cycle (in particular, TGFβ, STAT, and RAS pathways) compared with mpMRI-invisible tumours; however, this was unadjusted for multiple testing and this study scored relatively low using the modified Newcastle-Ottawa scale (3/8), indicating a potential a risk of bias. Finally, Beksac et al [17] reported that pathways associated with CCP (PI3K-AKT-mTOR and E2F) and castration resistance (WNT-b) were found to be more active in mpMRI-visible cancer (PI-RADSv2 score of 5) than in mpMRI-invisible cancer.…”
Section: Evidence Synthesismentioning
confidence: 60%
“…42 We previously identified DNA damage as a key element of the genetic determinants of tumor visibility on mpMRI, from previous studies that demonstrated that tumors with higher DCE values (ie, tumors that are visible on the contrast mpMRI sequence) had significantly higher deregulation of DNA repair-related genes, compared to tumors with lower DCE values. 43 Li and colleagues also found that DNA damage repair pathway abnormalities were enriched in mpMRI-visible tumors. 33 Together, these studies provide support for our hypothesis, given that pronounced DNA repair abnormalities found in mpMRI-visible disease are likely to contribute to an adverse clinical prognosis.…”
Section: Dna Damage and Repairmentioning
confidence: 96%
“…Tumor hypoxia is known to downregulate DNA double strand break repair gene expression in prostate cancer cells such as: Rad51, Rad52, Rad54, BRCA1, BRCA2 , leading to an increase in DNA damage 42 . We previously identified DNA damage as a key element of the genetic determinants of tumor visibility on mpMRI, from previous studies that demonstrated that tumors with higher DCE values (ie, tumors that are visible on the contrast mpMRI sequence) had significantly higher deregulation of DNA repair‐related genes, compared to tumors with lower DCE values 43 . Li and colleagues also found that DNA damage repair pathway abnormalities were enriched in mpMRI‐visible tumors 33 .…”
Section: Supportive Evidencementioning
confidence: 99%
“…However, we believe the “glass is half full”. While these tests may not overcome the issue of heterogeneity, they do address it and provide a level of risk stratification beyond pathology alone that can be helpful in select cases ( 46 ).…”
Section: Prostate Cancer Heterogeneity and Concern For Genomicsmentioning
confidence: 99%